Pengaruh Latihan High Hurdle Jump Into a Sprint dengan Latihan Lateral Hurdle Jump a Into Sprint Terhadap Peningkatan Kelincahan - Mubarok, Aziz Khusnul; Maryati, Sri; Kardani, Gani (Jurnal Keolahragaan, 2023)
The purpose of this study was to evaluate the effect of high hurdle jump into sprint training and lateral hurdle jump into sprint training on increased agility. The research method used is an experimental method. The method used is by the research carried out, namely to find the influence of the form of high hurdle jump into sprint training with the form of lateral hurdle jump into sprint training at SMK Komputama Majenang Cilacap Regency. Based on the results of data analysis that has been carried out, the author concludes that high hurdle jump into a sprint and lateral hurdle jumps into a sprint can significantly increase agility in SMK Komputama Cilacap Regency students. Therefore, both types of exercises can be used as an effective modification of agility training for students of SMK Komputama Cilacap Regency or other individuals who want to improve their physical abilities in terms of agility.